Analysis of the Quantity and Quality of Water in the Piru City Area, Seram Bagian Barat Regency - Gudam, Frengki; Riry, Roberth Berthy; Pinoa, Wiclif Sephnath (JENDELA PENGETAHUAN, 2024)
This research aims to assess the potential quality and quantity of groundwater in Piru City and its surrounding areas. The survey method involving primary and secondary data analysis was employed, including satellite imagery, thematic maps, and field observations. The key findings are as follows: (1) The potential quantity of groundwater in the research location is approximately 40,512 x 10^6 m³year-1, supporting the demand for clean water until 2020. (2) The quality of groundwater varies, with some portions deemed unsuitable for consumption, particularly in the Waetemen coastal area (high Fe) and Markas complex (low pH). However, the overall water quality remains suitable for agricultural purposes, and it is categorized into three groups with different risks of alkalinity and salinity. (3) Based on the groundwater potential, recommendations include utilization for drinking water, urban development, and agriculture, especially in alluvial plains with high potential in the unconfined aquifer. Conservation zones should be implemented in gently sloping hill areas. In conclusion, this research provides crucial insights for groundwater management and regional development, particularly considering the rapid population growth.